2015
DOI: 10.1002/etc.2905
|View full text |Cite
|
Sign up to set email alerts
|

Larval exposure to polychlorinated biphenyl 126 (PCB‐126) causes persistent alteration of the amphibian gut microbiota

Abstract: Interactions between gut microbes and anthropogenic pollutants have been under study. The authors investigated the effects of larval exposure to polychlorinated biphenyl 126 (PCB-126) on the gut microbial communities of tadpoles and frogs. Frogs treated with PCBs exhibited increased species richness in the gut and harbored communities significantly enriched in Fusobacteria. These results suggest that anthropogenic pollutants alter gut microbial populations, which may have health and fitness consequences for ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…We hypothesize that exposure to atrazine changes gut bacterial communities of hosts because this pattern has been observed with other pollutants (Fig. 1, path c ) (Shehata et al 2013; Theriot et al 2014; Kohl et al 2015) and atrazine interacts with bacteria in the environment (Newcombe & Crowley 1999). If atrazine does alter the microbiota, we hypothesize that these changes in microbiota will be associated with changes in defenses against Bd (Fig.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…We hypothesize that exposure to atrazine changes gut bacterial communities of hosts because this pattern has been observed with other pollutants (Fig. 1, path c ) (Shehata et al 2013; Theriot et al 2014; Kohl et al 2015) and atrazine interacts with bacteria in the environment (Newcombe & Crowley 1999). If atrazine does alter the microbiota, we hypothesize that these changes in microbiota will be associated with changes in defenses against Bd (Fig.…”
Section: Introductionmentioning
confidence: 65%
“…1, path c ). Other studies have found an effect of pollutants, such as PCBs and antibiotics, on microbial communities (Shehata et al 2013; Theriot et al 2014; Kohl et al 2015; Schwarz et al 2016), but in several cases, the concentrations of these chemicals were quite high. There are several potential reasons why atrazine exposure did not affect the microbiota of tadpoles or adults.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…That is, an early-life disruption of human microbiota might stimulate an under-reactive immune response to infections, in addition to the previously established over-reactive immune response to innocuous agents (allergens and host) 13 . Furthermore, several factors, such as pollutants (including antibiotics) 2, 21, 22 , nutrition 23–25 , and climate 26 can disrupt the microbiota of animal hosts, and as a consequence, they might affect infectious disease risk 27, 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Given what we know regarding early life antibiotic exposure [40], might the timing of AHR activation in the gut or the skin or lung influence the microbiota as it establishes itself early in the life of the host? Interestingly, Lithobates pipiens larval exposure to PCB-126 resulted in significant and permanent changes in the gut microbiota of adult frogs [41]. However, it is not clear if these effects were mediated by direct impact on the microbiota or driven by host physiology.…”
Section: Future Studies To Advance Our Understanding Of Ahr Activity mentioning
confidence: 99%